Autoimmune mechanisms in Guillain-Barré syndrome subtypes: a systematic review - O. I. Oshomoji; J. O. Ajiroba; S. O. Semudara; M. A. Olayemi; S. O. Adeoye (Bulletin of Faculty of Physical Therapy, 2024)
Abstract Guillain-Barré syndrome (GBS) is a complex autoimmune disorder characterized by acute onset of motor weakness, often following an infectious illness. The pathophysiology of GBS involves a multifaceted interplay between immune mechanisms and environmental factors, leading to demyelination or axonal degeneration. This systematic review aims to elucidate the autoimmune mechanisms underlying the various subtypes of GBS, including acute inflammatory demyelinating polyneuropathy (AIDP), acute motor axonal neuropathy (AMAN), acute motor and sensory axonal neuropathy (AMSAN), and Miller Fisher syndrome (MFS). A thorough literature search identified 71 studies published between 2010 and 2024 that provided insights into the immunopathological features, clinical implications, and future directions for research. Key findings indicate that specific autoantibodies, such as anti-GM1 and anti-GQ1b, are associated with distinct subtypes of GBS, contributing to the disease’s heterogeneity. Understanding these autoimmune mechanisms is crucial for improving diagnostic accuracy, therapeutic strategies, and prognostic indicators in GBS. This review highlights significant gaps in current research, emphasizing the need for further studies to explore the genetic and environmental factors that influence GBS susceptibility and the role of vaccinations in triggering autoimmune responses.  Trial registration PROSPERO CRD42024606718.